Fracture behavior of natural fiber-reinforced cemented paste backfill under mode-I, mode-II, and mode-III loading: Effect of fiber content and fiber length - Hartford, Michael (My University, 2024)
The mechanical stability of mine backfill materials is crucial for the safety of mining personnel and production efficiency. When placed into mined-out voids, known as stopes, mine backfill materials are required to provide reliable secondary ground support, which is subjected to finite deformation loading, especially in deep mines. However, due to the quasi-brittle characteristics of cemented paste backfill (CPB), these materials possess very limited post-peak resistance. Enhancing the post-peak engineering performance of CPB is achievable through natural fiber reinforcement techniques. In this study, hemp fibers were selected for their abundant availability in Canada. To investigate their effectiveness in terms of fiber reinforcement, four different fiber lengths (5mm, 10mm, 20mm, and 30mm) and four fiber contents (0.25wt%, 0.5wt%, 1wt%, and 1.5wt%) were employed to prepare the natural fiber-reinforced CPB (NFR-CPB). A series of mechanical tests, including semicircular bend (SCB) tests and end-notched disc bend (ENDB) tests, along with scanning electron microscope (SEM) observations, were conducted on NFRCPB and control CPB (without fiber reinforcement) at 7 days, 28 days, and 90 days. The results revealed that hemp fiber reinforcement can influence pre-peak behavior and effectively enhance post-peak resistance. Additionally, the results showed that increasing the hemp fiber content and length improved the fracture energy, ductility, and fracture toughness of NFR-CPB. Therefore, the proposed hemp fiber reinforcement approach can be considered a promising method for CPB technology in deep mining applications.